Organismal benefits of transcription speed control at gene boundaries. (27th February 2020) - Leng, Xueyuan; Ivanov, Maxim; Kindgren, Peter; Malik, Indranil; Thieffry, Axel; Brodersen, Peter; Sandelin, Albin; Kaplan, Craig D; Marquardt, Sebastian
Abstract: RNA polymerase II (RNAPII) transcription is crucial for gene expression. RNAPII density peaks at gene boundaries, associating these key regions for gene expression control with limited RNAPII movement. The connections between RNAPII transcription speed and gene regulation in multicellular organisms are poorly understood. Here, we directly modulate RNAPII transcription speed by point mutations in the second largest subunit of RNAPII in Arabidopsis thaliana . A RNAPII mutation predicted to decelerate transcription is inviable, while accelerating RNAPII transcription confers phenotypes resembling auto‐immunity. Nascent transcription profiling revealed that RNAPII complexes with accelerated transcription clear stalling sites at both gene ends, resulting in read‐through transcription. The accelerated transcription mutant NRPB2‐Y732F exhibits increased association with 5′ splice site (5′SS) intermediates and enhanced splicing efficiency. Our findings highlight potential advantages of RNAPII stalling through local reduction in transcription speed to optimize gene expression for the development of multicellular organisms. Synopsis: RNAPII mutations that accelerate transcription cause auto‐immunity‐like phenotypes, read‐through transcription at RNAPII stalling sites and enhanced splicing in Arabidopsis, indicating that controlled transcription speed is required for optimal gene expression and plant development. A point mutation in RNAPII that increases the speed of RNAPII transcription triggers auto‐immunity‐like phenotypes. plaNET‐seq reveals reduced RNAPII stalling at gene boundaries in fast transcription mutants. Increasing the speed of transcription reduces the efficiency of transcriptional termination, resulting in read‐through transcription that blurs the spatial separation of genes. Accelerating RNAPII transcription enhances splicing efficiency in the multi‐cellular context. Abstract : RNAPII mutations that accelerate transcription cause auto‐immunity‐like phenotypes, read‐through transcription at RNAPII stalling sites and enhanced splicing in Arabidopsis, indicating that controlled transcription speed is required for optimal gene expression and plant development.